The paragenesis of silver minerals in the Pb-Zn Stan Terg deposit, Kosovo: an example of precious metal epithermal mineralization - Kołodziejczyk, Joanna; Pršek, Jaroslav; Asllani, Burim; Maliqi, Feriz (Geology, Geophysics and Environment, 2016)
This study reports silver mineral association found recently in the Stan Terg lead and zinc mine, located in the Vardar zone (in northern Kosovo). The described mineralization comprises pyrargyrite (Ag3SbS3), freieslebenite (AgPbSbS3), high-Ag bearing tetrahedrite and freibergite ((Ag4+2xCu2−2x )[(Cu,Ag)4(Fe, Zn)2]Σ6Sb4S12S1−x with (0 < x < 1)); as well as native compounds (Electrum, composition of those minerals was confirmed by the electron microprobe. The freibergite from native silver is native antimony). The Ag-minerals occur in vuggs and cracks in a massive galena ore and have signs of the latest minerals, which precipitated in the deposit. The chemical of the Stan Terg deposit reveals zonality and contains between 13.91–20.28% of Ag. The high concentration of Ag in solutions is also indicated by relatively high silver content in Au-Ag alloy (electrum), which is between 47.02% and 73.19% of Ag. The Ag association is supposed to be an epithermal equivalent of precious metal mineralization, which could be located in the external part of the Stan Terg hydrothermal system. This association occurs in low temperatures, below 200°C. The Ag-minerals can be a part of epithermal veins from the external part of the Stan Terg hydrothermal system. Similarly to the other known Pb-Zn-Ag hydrothermal systems, the Ag association is related to the formation of the rhodochrosite banded ore and Ag-Au-Sb dominated mineralization.